INTERPRETATION OF SELF-POTENTIAL ANOMALIES FOR INVESTIGATING FAULT USING THE LEVENBERG-MARQUARDT METHOD A STUDY CASE IN PINGGIRSARI, WEST JAVA - (NIM: 20214033), FAJRIANI
Self potential (SP) method is often used to identify subsurface structures, both of which use a continuous and fixed geometry model. For fixed geometry, SP method related to geometric shape from buried structure such as sphere, cylinder, and sheet. Implementation of this method is determines the value of parameters such as the shape, depth, polarization angle, and electric dipole moment which causes anomalies in the surface. In this work, the method will be applied to identify for the existence of fault, where the fault is considered to resemble the shape of the sheet. The field data used to estimate sheet parameters by inversion modeling used approaches Levenberg-Marquardt method. The first stage begins with a test the inverse program using synthetic data, where a close agreement between the presumed and calculated parameters was obtained. After that, the inversion program is used for field data. The result shows that calculated data follows the pattern of anomalies. The final data processing showed the presence of fault both the location and the value of parameters.